MACHINES FOR PRIMARY LOG CUTTING: PART II – COMPARATIVE ASSESSMENTS AND ANALYSIS - Atanasov, Valentin (Innovation in Woodworking Industry and Engineering design, 2025)
In the paper a developed methodology is presented, which will be useful in a comparison between individual machines for primary cutting of logs – a vertical band saw machine with a carriage feed mechanism (Üstünkarli – Turkey), circular saw machine for logs (Kallion Konepaja Oy – Finland) and a mobile horizontal band saw machine (Arsov 90 Ltd. – Bulgaria). On the basis of the obtained experimental results, which are presented in the first part of the current study and the technical parameters of the machines, the following evaluation indicators were selected: productivity, dimensional accuracy, roughness of the obtained surfaces, width of the cut, required power, cutting tools, etc. The obtained quantitative results were transformed into point scores. For each of the indicators, a weighting coefficient is also selected, depending on its importance. The advantages and disadvantages of the studied machines are indicated and an analysis of the results is carried out.